Melatonin increases AKT and SOD gene and protein expressions in diabetic rats - Mohamed Lotfy; Aalaa Khattab; Mohammed Shata; Ahmad Alhasbani; Abdallah Khalaf; Saeed Alsaeedi; Mahdi Thaker; Hazza Said; Harun Tumi; Hassan Alzahmi; Omar Alblooshi; Mohamad Hamdan; et al. (Heliyon, 2024)
Diabetes mellitus (DM) is a chronic metabolic disease marked by hyperglycemia due to insulin deficiency or insulin resistance leading to many chronic complications. It is thus important to manage diabetes effectively in order to prevent and or delay these complications. Melatonin is produced by the pineal gland and regulates the wake-sleep circadian rhythm. Existing evidence suggests that melatonin may be effective in the management of DM. However, the evidence on the mechanism of the beneficial effect melatonin as a treatment for DM is limited. In this study, we investigated the effect of melatonin treatment on blood glucose, insulin (INS), AKT and superoxide dismutase (SOD) gene levels in diabetic rats. Non-diabetic and diabetic rats were treated orally for 4 weeks with either 25 mg or 50 mg/kg body weight of melatonin. At the end of the study, pancreatic and liver tissues morphology, glucose homeostasis, serum insulin and SOD levels, hepatic gene and protein expression of SOD as protecting antioxidant enzyme and AKT as central element involved in PI3K/AKT insulin signaling pathway were estimated. Melatonin treated diabetic rats showed reduced hyperglycemia, and increased serum insulin and SOD levels. In addition, melatonin induced an increased gene and protein expression of SOD and AKT. In conclusion, melatonin may play a role in treating diabetic rats via stimulation of insulin secretion, insulin signaling and reduction in oxidative stress.